The role of nitric oxide and adrenergic stimulation on the cardiovascular adjustments in South American rattlesnakes (Crotalus durissus) - Castro, Samanta Aparecida (2019)
Understanding the basis of vascular tone regulation is important to comprehend the cardiovascular physiology of any vertebrate. Recent investigations on reptiles have tried that description working on anesthetized animals. Unfortunatelly, such approach can be ineffective to access mechanisms that rely on some level of autonomic modulation. The aim of this study was to investigate the role of nitric oxide (NO) and of adrenergic stimulation on the control of vascular tone in reptiles. This study used the developed decerebrate rattlesnake model in order to avoid the deleterious effect of anesthetics on cardiovascular modulation. We found that NO is effective vasorelaxing in rattlesnakes and there is a resting level of NO production. Sodium nitroprusside (SNP) caused systemic vasodilation followed by systemic conductance (Gsys) and systemic flow (Q ̇sys) increasing, and it was associated with systemic mean arterial pressure (MAPsys) reduction. As a response, cardiac output (CO) was elevated. In the pulmonary circulation, SNP increased pulmonary conductance (Gpul) and reduced pulmonary mean arterial pressure (MAPpul), while pulmonary flow (Q ̇pul) remained unaffected. The systemic vasodilation after L-arginine (L-Arg) was similar to the effect of SNP injection. Although, there were no effects of L-Arg on the pulmonary circulation. Therefore, in rattlesnakes, NO is synthetized via L-Arg and it has partial role on the local regulation of systemic vascular tone. In contrast, the pulmonary vasculature is less reactive to SNP and also, NO production seems not to be dependent on the L-Arg. Adrenaline and phenylephrine caused systemic vasoconstriction that was abolished by phentolamine, demonstrating this response was mediated by α-adrenergic receptors. Injection of phentolamine caused a marked vasodilatation followed by Gsys and Q ̇sys increasing, and it was associated with MAPsys reduction. Injection of propranolol promoted bradycardia, with consequent decreasing of CO and Q ̇sys and increased of systemic vascular tone, without changing the Gsys and MAPsys. These results indicate adrenergic modulation via α-receptors is quantitativelly more relevant to modulate MAP than the β-receptors branch of barorreflex in Crotalus. Pulmonary vasculature is less responsive to adrenergic stimulation. Also, phentolamine was more effective in alter Gpul than propranolol. Therefore, we suggest that the adrenergic stimulation by the sympathetic branch of the autonomic nervous system is more effective in modulate vascular tone than cardiac activity in rattlesnakes.